Synthesis and biological evaluation of some novel triazole hybrids of curcumin mimics and their selective anticancer activity against breast and prostate cancer cell lines. Issue 17 (1st September 2016) - Mandalapu, Dhanaraju; Saini, Karan S.; Gupta, Sonal; Sharma, Vikas; Yaseen Malik, Mohd.; Chaturvedi, Swati; Bala, Veenu; Hamidullah; Thakur, Subhadra; Maikhuri, Jagdamba P.; Wahajuddin, Muhammad; Konwar, Rituraj; et al.
Graphical abstract: Highlights: Curcumin mimic–1, 2, 3-triazole conjugates with two prototypes were synthesized. Compounds17 and26 displayed significant anticancer activity than curcumin. Compounds17 and26 induced mitochondrial-mediated apoptosis and cell cycle arrest. Also significantly down regulated phospho-Akt, PCNA, Bcl-2 and upregulated Bax. Abstract: The anti-cancer property of curcumin, an active component of turmeric, is limited due to its poor solubility, stability and bioavailability. To enhance its efficacy, we designed a novel series of twenty-four monocarbonyl curcumin analogue–1, 2, 3-triazole conjugates and evaluated their anti-cancer activity towards endocrine related cancers. The new compounds (17 –40 ) were synthesized through CuAAC click reaction and SAR analysis carried out. Out of these all, compound17 showed most significant anti-cancer activity against prostate cancer cells with IC50 values of 8.8 μM and 9.5 μM in PC-3 and DU-145 cells, respectively. Another compound26 showed significant anti-cancer activity against breast cancer cells with IC50 of 6 μM, 10 μM and 6.4 μM in MCF-7, MDA-MB-231 and 4T1 cells, respectively while maintaining low toxicity towards non-cancer originated cell line, HEK-293. Compounds17 and26 arrested cell cycle and induced mitochondria-mediated apoptosis in cancer cells. Further, both of these compounds significantly down-regulated cell proliferation marker (PCNA), inhibited activation of cell survival protein (Akt phosphorylation), upregulated pro-apoptotic protein (Bax) and down-regulated anti-apoptotic protein (Bcl-2) in their respective cell lines. In addition, in vitro stability, solubility and plasma binding studies of the compounds17 and26 showed them to be metabolically stable. Thus, this study identified two new curcumin monocarbonyl–1, 2, 3-triazole conjugate compounds with more potent activity than curcumin against breast and prostate cancers.